Pengaruh Kualitas Produk dan Harga terhadap Keputusan Pembelian Pakaian Thirfting pada Generasi Z di Singaraja - Ni Kadek Suci Listriani; Ni Wayan Ayu Santi (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyse the effect of product quality and price on purchasing decisions for thrifting clothing for generation Z in Singaraja. The population of this study is thrifting clothing consumers aged 18-27 years. The location of this research was conducted in Singaraja involving 130 generation Z aged 18 to 27 years as respondents. The sample technique used was nonprobability sampling technique with purposive sampling method. The data in this study were collected by means of online and offline questionnaires. The analysis technique used in this research is multiple linear regression analysis with partial (t test) and simultaneous (F test) hypothesis testing. The results of this study indicate that (1) Product quality has a significant positive effect on purchasing decisions for thrifting clothing for generation Z in Singaraja, with a significance value of 0.000 <0.05. (2) Price has a significant effect on the purchase decision of thrifting clothes for generation Z in Singaraja with a significance value of 0.000 <0.05. And (3) product quality and price have a significant influence on the purchase decision of thrifting clothes for generation Z in Singaraja, which is indicated by the results of simultaneous tests, namely product quality (X1) and price (X2) have Fhitung 62.051> Ftabel 3.07 with a significance value of 0.000 <0.05.